Gold-amine cooperative catalysis for reductions and reductive aminations using formic acid as hydrogen source - Fiorio, Jhonatan L.; Araújo, Thaylan P.; Barbosa, Eduardo C. M.; Quiroz, Jhon; Camargo, Pedro H. C.; Rudolph, Matthias; Hashmi, A. Stephen K.; Rossi, Liane M. (Applied catalysis. B, Environmental, 2020)
Selective hydrogenation of alkynes to alkenes and reductive amination are industrially important reactions to synthesize a variety of fine and bulk chemicals. We report herein on a green and convenient approach for Z-alkenes and secondary amines using gold catalyst and formic acid (FA) as a green reductant. Furthermore, we highlight that the key to successfully obtain high reaction rates is to use an appropriate amine, which acts cooperatively with the gold surface, to activate formic acid. Studies with deuterium-labeled hydrogen donors gave insights that the decomposition of Au-formate species is involved in the rate-determining step. Moreover, various valuable secondary amines could be synthetized from readily available nitro and carbonyl compounds. This new strategy provides a cleaner, safer, more efficient and selective way to catalyze the synthesis of Z-alkenes and valuable amines.